2012
DOI: 10.1515/1469-3569.1391
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Political Donations: Investment or Agency?

Abstract: We examine corporate donations to political candidates for federal offices in the United States from 1991 to 2004. Firms that donate have operating characteristics consistent with the existence of a free cash flow problem, and donations are negatively correlated with returns. A $10,000 increase in donations is associated with a reduction in annual excess returns of 7.4 basis points. Worse corporate governance is associated with larger donations. Even after controlling for corporate governance, donations are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(150 citation statements)
references
References 31 publications
2
134
0
1
Order By: Relevance
“…However, two studies (Bliss & Gul, 2012;Fan et al, 2007) reported a negative impact of CPA on performance in Malaysia and China. Similarly two studies (Aggarwal et al, 2011;Hadani & Schuler, 2013) reported negative outcomes of CPA in the United States. Two other studies (Ansolabehere et al, 2004;Hersch et al, 2008) found no significant impact.…”
Section: <Insert Figure 2>mentioning
confidence: 94%
See 1 more Smart Citation
“…However, two studies (Bliss & Gul, 2012;Fan et al, 2007) reported a negative impact of CPA on performance in Malaysia and China. Similarly two studies (Aggarwal et al, 2011;Hadani & Schuler, 2013) reported negative outcomes of CPA in the United States. Two other studies (Ansolabehere et al, 2004;Hersch et al, 2008) found no significant impact.…”
Section: <Insert Figure 2>mentioning
confidence: 94%
“…Using United States data, Aggarwal et al (2011) found that "soft money" donations are negatively correlated with returns. They also found that donating firms acquire more and record lower abnormal returns on acquisition announcements.…”
Section: Negative Performance Outcomesmentioning
confidence: 99%
“…In contrast, Aggarwal et al. () found that that companies that made soft money donations to parties or donations to Section 527 committees from 1991 to 2004 (accounting for roughly 11 percent of the universe of U.S. publicly traded firms) tended to be large, slowly growing firms that had more free cash than other firms but spent less on research and development or business investments. They also found that corporate donations were negatively correlated with long‐term firm‐specific stock market performance.…”
Section: Legal Context and Prior Literaturesmentioning
confidence: 98%
“…Empirical evidence is also mixed.There is evidence in support for both positive (Cooper, Gulen, & Ovtchinnikov, 2010;Fisman, 2001;Frynas, Mellahi, & Pigman, 2006;Goldman, Rocholl, & Jongil So, 2009;Jayachandran, 2006) and negative (Aggarwal, Meschke, & Wang, 2012a;Ansolabehere, De Figueiredo, & Snyder Jr., 2003;Hadani & Schuler, 2013a;Hersch, Netter, & Pope, 2008;Okhmatovskiy, 2010;Siegel, 2007;Sun, Wright, & Mellahi, 2010) effect of CPA on business performance. (Tian, Hafsi, & Wu, 2009) suggest that even in emerging economies the effectiveness of CPA is not uncontested.…”
Section: Performance Outcomes Of Cpamentioning
confidence: 99%